Microstructure and low cycle fatigue of a Ti2AlNb-based lightweight alloy. (1st May 2020) - Zhang, Yinling; Feng, Aihan; Qu, Shoujiang; Shen, Jun; Chen, Daolun
Abstract: Ti2 AlNb-based intermetallic compounds are considered as a new category of promising lightweight aerospace materials due to their balanced mechanical properties. The aim of this study was to evaluate monotonic and cyclic deformation behavior of an as-cast Ti-22A1-20Nb-2V-1Mo-0.25Si (at.%) intermetallic compound in relation to its microstructure. The alloy containing an abundant fine lamellar O-Ti2 AlNb phase exhibited a good combination of strength and plasticity, and superb fatigue resistance in comparison with other intermetallic compounds. Cyclic stabilization largely remained except slight cyclic hardening occurring at higher strain amplitudes. While fatigue life could be described using the common Coffin-Mason-Basquin equation, it could be better predicted via a weighted energy-based approach. Fatigue crack growth was characterized mainly by crystallographic cracking, along with fatigue striation-like features being unique to appear in the intermetallics. The results obtained in this study lay the foundation for the safe and durable applications of Ti2 AlNb-based lightweight intermetallic compounds.